Cryopreservation of oocytes as a method of implementing reproductive plans in women with cervical cancer - Dorofieieva, Valeriia; Kapustnyk, Nataliia (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):247